Exotic Dramatic Style Pada Busana Ready To Wear Dengan Aplikasi Ornamen Jagar-Jagar Mandailing Sumatera Utara - Dinda Atthia Maharani Lubis; Dini Yanuarmi (Penerbit dan Percetakan, CV. Picmotiv, 2025)
The work titled 'Exotic Dramatic Style with the Application of Jagar-jagar Ornaments from Mandailing, North Sumatra' is a creation of fashion that carries an exotic dramatic style. Exotic dramatic style is known for its unique, ethnic, and dramatic characteristics that highlight visual strength through contrasting colors such as red, black, and white. The jagar-jagar ornament is located on the peak of the traditional house (bagas godang). The jagar-jagar ornament from Mandailing has a shape resembling a cross or the letter X, arranged repeatedly. In this creation, a ready-to-wear type of clothing is presented. This clothing is realized through a combination of high-quality materials such as bridal satin, linen, and clara fabric. To showcase the raised jagar-jagar ornaments, a modification of the surface cording technique is used. The surface cording technique is a manipulation of fabric or material engineering technique that applies cords or edges on the surface of the fabric to create decorative patterns. The design process begins with field exploration and the creation of designs that refer to heritage trends in trend forecasting 2024/2025. The creation of this fashion is not only an art piece but also a medium for cultural preservation, enhancement of appreciation for traditional fabrics, and an effort to introduce cultural heritage to the modern realm. This work is expected to foster a sense of pride in cultural identity, broaden perspectives in the world of fashion, and inspire the younger generation to develop clothing based on local culture. The final result of the ready-to-wear collection is titled Saroha. This clothing represents the harmony between Mandailing culture and modern style, blended into a single fashion piece.